Scaling factors for the in vitro–in vivo extrapolation (IV–IVE) of renal drug and xenobiotic glucuronidation clearance. (14th March 2016) - Knights, Kathleen M.; Spencer, Shane M.; Fallon, John K.; Chau, Nuy; Smith, Philip C.; Miners, John O.
Abstract : Aim: To determine the scaling factors required for inclusion of renal drug glucuronidation clearance in the prediction of total clearance via glucuronidation (CLUGT ). Methods: Microsomal protein per gram of kidney (MPPGK) was determined for human 'mixed' kidney ( n = 5) microsomes (MKM). The glucuronidation activities of deferiprone (DEF), propofol (PRO) and zidovudine (AZT) by MKM and paired cortical (KCM) and medullary (KMM) microsomes were measured, along with the UGT 1A6, 1A9 and 2B7 protein contents of each enzyme source. Unbound intrinsic clearances (CLint, u, UGT ) for PRO and morphine (MOR; 3‐ and 6‐) glucuronidation by MKM, human liver microsomes (HLM) and recombinant UGT1A9 and 2B7 were additionally determined. Data were scaled using in vitro – in vivo extrapolation (IV–IVE) approaches to assess the influence of renal CLint, u, UGT on the prediction accuracy of the calculated CLUGT values of PRO and MOR. Results: MPPGK was 9.3 ± 2.0 mg g −1 (mean ± SD). The respective rates of DEF (UGT1A6), PRO (UGT1A9) and AZT (UGT2B7) glucuronidation by KCM were 1.4‐, 5.2‐ and 10.5‐fold higher than those for KMM. UGT 1A6, 1A9 and 2B7 were the only enzymes expressed in kidney. Consistent with the activity data, the abundance of each of these enzymes was greater in KCM than in KMM. The abundance of UGT1A9 in MKM (61.3 pmol mg −1 ) was 2.7 fold higher than that reported for HLM. Conclusions: Scaled renal PRO glucuronidation CLint, u, UGT was double that of liver. Renal CLint, u, UGT should be accounted for in the IV–IVE of UGT1A9 and considered for UGT1A6 and 2B7 substrates.